Introduction to the Dossier “Music and periodical press in Latin America: Cultural Processes and Interdisciplinarity” (Revista Argentina de Musicología, 2025)
Editorial
Keywords: music and periodical press; feminist musicology; folklorism; interdisciplinarity; nationalism